LIQUEFACTION ANALYSIS ON THE RUNWAY AND PARALLEL TAXIWAY AT SENTANI JAYAPURA AIRPORT - Widodo, Bambang (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2024)
Infrastructure development with a relatively large project value and functioning buildings is very important, so planning needs to be reviewed from various aspects. One very important aspect is the geotechnical aspect. Part of the geotechnical aspect is safety against liquefaction hazards. Liquefaction is a natural event that depends on the location of the building around the earthquake zone, the topography around the building, and the type of soil layer that supports the building. A liquefaction hazard analysis was conducted to determine the cost of repairing the subgrade supporting the runway and parallel taxiway structures in the detailed engineering design work to meet airport-side facility standards at Sentani Jayapura Airport. The methodology used was to conduct a soil test at the research location with a machine drill of 22 points (21 points at a depth of 15 meters and 1 point at a depth of 30 m), and a Sonder test (CPT) at 19 points at the research location. The next stage is plotting the location on the earthquake zone map, topographical observations, and information on the geological conditions around the study site. Liquefaction analysis uses several references. The results of the study show that liquefaction relatively does not occur at locations that are built parallel and taxiways, so there is no need for subgrade improvement costs. Keyword: liquefaction hazard analysis, earthquake engineering, airport infrastructure, soil analysis